The Effects of TCu-380 on Cervicovaginal Flora - Mine Kanat Pektaş; Tayfun Güngör; Yaşar Şahin (Medical Network, 2007)
OBJECTIVE: This study aims to identify the alterations in cervicovaginal flora after insertion of TCu 380A which is a popular type of copper IUD. STUDY DESIGN: Among the women who attended to the Department of Family Planning in our hospital during a month, 100 subjects who preferred IUDs for contraception and had no history of local or systemic antibiotic use were eligible. RESULTS: Anaerobic colonies, especially Gram positive cocci and Gram negative bacilli were isolated at significantly higher rates after the insertion of TCu-380A. Aerobic colonies were isolated relatively but insignificantly less. CONCLUSIONS: Being consistent with the literature, it can be suggested that the copper IUD causes the predominance of anaerobic species in the cervicovaginal flora. This clinically insignificant condition can be attributed to the copper content or threads of the IUDs. Yet there is no evidence that the prevalance of pelvic infections is influenced by the use of IUDs.